2012
DOI: 10.1002/micr.21994
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluating the paradigm of early free flap coverage in lower extremity trauma

Abstract: Early free flap coverage in lower extremity trauma is a practice largely supported by research that may be outdated and is frequently impractical due to logistics, resuscitation efforts, and associated injuries. Our objective was to re-evaluate this paradigm to determine whether reconstructive timing impacts outcome in modern clinical practice. We reviewed 60 free flaps for traumatic lower extremity coverage from December 2005 to December 2010 by the plastic surgery service at an academic medical center. All r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…Effective coverage of the bone, tendon, ligament, muscle, nerve, and metallic material, however, helps to reduce the rate of infection, bone, and soft tissue necrosis, and promotes bone healing. This is especially important for injury around the knee, which has a higher rate of complication if inadequate coverage has occurred [1][2][3][4]. The reverse anterolateral thigh flap technique, which is supplied by the cutaneous perforator from the db-LCFA and anastomosis with the SLGA, was introduced and improves the outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective coverage of the bone, tendon, ligament, muscle, nerve, and metallic material, however, helps to reduce the rate of infection, bone, and soft tissue necrosis, and promotes bone healing. This is especially important for injury around the knee, which has a higher rate of complication if inadequate coverage has occurred [1][2][3][4]. The reverse anterolateral thigh flap technique, which is supplied by the cutaneous perforator from the db-LCFA and anastomosis with the SLGA, was introduced and improves the outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
“…There were also limited vascularisation techniques due to the complexity of the operation and postoperative care. Failure of primary treatment causes more damage to the surrounding tissue and increases cost of the overall treatment [1][2][3]. The technique of reverse-flow anterolateral thigh (ALT) flap was first described by Zhang [7] in 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hill et al reviewed their series of 60 free flaps for lower extremity reconstruction to evaluate the effect of timing of wound coverage on outcomes. They found no difference in outcomes comparing patients undergoing reconstruction < 30 days, 31–90 days and > 90 days after injury and concluded that the historical data that suggested an advantage to early flap coverage (< 72 hours) may no longer be relevant given advances in wound care, debridement techniques, broad spectrum antibiotics and the advent of negative pressure dressings 24 . We tend to agree with this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional teaching holds that early coverage of lower extremity defects has been associated with a lower risk of complications, [3][4][5] although recent data may dispute this. 6,7 OPTIONS FOR COVERAGE When considering the different methods to use for covering a lower extremity wound, we must balance the desire to have timely, reliable, durable coverage with the need to minimize complications and donor site morbidity. There are several different versions in the literature of a "reconstructive ladder" for wound closure or coverage.…”
Section: Preoperative Planningmentioning
confidence: 99%